Perancangan User Experience Aplikasi Pembelajaran Marketplace terhadap Pengusaha UMKM dengan Metode Human-Centered Design - Swastika Akbar Umardani; Ratih Kartika Dewi; Komang Candra Brata (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2022)
During the pandemic, MSMEs find it very difficult to sell their products offline. Because of this, at this time offline sales have begun to be replaced with online purchases. MSMEs have been provided with a place to sell their goods, namely the marketplace. However, in Indonesia, there are many marketplaces that have developed. The number of marketplaces makes users confused because each marketplace has a different way of opening accounts, selling products, and promoting. In addition, the absence of an analysis of the marketplace makes users confused in choosing which marketplace is suitable for selling their products. Therefore, designing a marketplace learning user experience will help overcome these problems as well as smooth learning about marketing in the marketplace. The human-centered design method is used in the design with the first several stages, namely literature study which is used to collect information from reading literature. Then next, analysis of the context of use used to analyze the characteristics of the user. After that, analyze user needs to find out what features the user needs in the design. Then after that, making a solution design in the form of a high-fidelity prototype design. After that, do testing by measuring how useful the application is, with usability testing and UEQ. Usability measures 3 aspects, namely the effectiveness level produces a value of 87.14%, the efficiency aspect produces a value of 95.9% and satisfaction of 77%. While testing with a user experience questionnaire resulted in an attractiveness value of 2.02, a perspicuity value of 1.91, an efficiency value of 1.90, a dependability value of 1.58, a stimulation value of 2.04, and a novelty value of 1.81. After that, the results of the test were carried out to improve the design of the solution so that the results were better.